Chitosan‐calcium alginate dressing promotes wound healing: A preliminary study - Zhao, Wan‐Yi; Fang, Qing‐Qing; Wang, Xiao‐Feng; Wang, Xiao‐Wei; Zhang, Tao; Shi, Bang‐Hui; Zheng, Bin; Zhang, Ding‐Ding; Hu, Yan‐Yan; Ma, Lie; Tan, Wei‐Qiang (Wound repair and regeneration, 2020)
Dressings are necessary during the process of wound healing. Since the early 1980s, several types of wound dressings have been produced, but they cannot always take into account some effects include antibacterial effect, wound healing promotion, and other properties. In this study, we would like to develop an effective dressing with the above properties, especially accelerating wound healing effect. A chitosan‐calcium alginate dressing (CCAD) was developed by coating mixture of chitosan with high‐low molecular weight on calcium alginate dressing (CAD). We investigated the structural characteristics of CCAD with Fourier‐transform infrared spectroscopy (FTIR) and electron microscopy. The cytotoxicity and antibacterial property were evaluated in vitro using CCK‐8 and inhibition zone method. Moisture retention was tested on the skin of Sprague‐Dawley (SD) rats, and wound healing studies were performed on a full‐thickness skin wound model in SD rats. CCAD showed good moisturizing and antibacterial properties with no cytotoxicity. CCAD could inhibit inflammation by decreasing IL‐6, and it could also promote angiogenesis by increasing VEGF, resulting in better wound healing than CAD. CCAD is a better choice in wound care due to its antibacterial property, biocompatibility, moisture retention, healing promotion, and non‐cytotoxicity characteristics.